Delayed Diagnosis of a Tracheobronchial Foreign Body: A Case Report on Peanut Shell Aspiration and Management Challenges - Aroli, Hazazi Nur Adli; Asyari, Ade (Fakultas Kedokteran, Universitas Andalas, 2026)
Introduction: Delayed diagnosis of tracheobronchial foreign body aspiration often leads to significant complications, including pneumonia and bronchiectasis. Symptoms of foreign body aspirations can mimic other respiratory conditions such as asthma, pneumonia, or viral croup, leading to misdiagnosis. Rigid bronchoscopy remains the gold standard for the removal of tracheobronchial foreign bodies. Objective: To understand the diagnosis and management of a delayed aspiration foreign body in tracheobronchial. Case Report: A 2 years old boy was brought by his parents to outpatient clinic ORL-HNS of Dr. M. Djamil Hospital Padang, with chief complaints difficulty in breathing with cough since a month before admission. The parents do not know exactly what kind of aspiration incident occurred; patient was diagnosed suspected foreign body “Peanut” on bronchus. The patient underwent foreign body extraction using rigid bronchoscope and flexible grasping forcep. Conclusion: Management of delayed foreign body aspiration needs to be done comprehensively, and treated on time, coordination between family, caregivers, specialists and knowledge about symptoms, risks and complications of aspiration foreign bodies should be better understood. Early detection and treatment can significantly reduce the risk of long-term respiratory problems, by using rigid bronchoscope and flexible forceps foreign bodies can be removed properly with minimal complications and good visualization